Diagnostic Accuracy of Ultrasound in Detection of Spina Bifida in the First and Second Trimester Using Post-Natal MRI as Gold Standard - Sajida Hukamdeen, Muhammad Arsalan, Sidra Seyal, Zahra Nasrullah, Sidra Ali, Humna Ashraf, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Antenatal ultrasound has been reported to be an effective tool for detecting neural tube defects including spina bifida. Moreover, major structural abnormalities can be detected by ultrasound examination, depending on the time of ultrasound scan. Objectives: To determine the diagnostic accuracy of ultrasound in detection of spina bifida in the first and second trimester using post-natal MRI as gold standard. Study Design: Descriptive, Cross-sectional study Study duration: 11th February 2019 to 10th August 2019 Settings: Department of Radiology, Jinnah Hospital, Lahore. Materials & Methods: A total of 125 pregnant patients/Gravida presenting in first trimester (11 to 13 weeks) & second trimester (14 to 22 weeks) assessed on dating scan, at risk for spina bifida were included. Women with pre-eclempsia and eclempsia determined on systolic BP > 140 and protein urea and history of congenital heart defects were excluded. A standard ultrasound scan was performed by the same Radiologist on the same ultrasound machine and any findings associated with the spina bifida would be noted & recorded on a predesigned Performa (Attached). Patients were followed till delivery and post-natal MRI was done to evaluate spina bifida. Presence of absence of spina bifida on USG & MRI was noted. Results: All the patients were subjected to first ultrasonography and then MRI. USG supported the diagnosis of spina bifida in 62 patients. MRI confirmed spina bifida in 63 cases. In USG positive cases, 58 were true positive and 04 were false positive. While in USG negative patients, 58 were true negative and 05 were false negative. Overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of ultrasound in detection of spina bifida in the first and second trimester using post-natal MRI as gold standard is 92.06%, 93.55%, 93.55%, 92.06% and 92.80% respectively. Conclusion: This study concludes that ultrasonography is a highly sensitive and accurate modality for diagnosing spina bifida, and has not only dramatically improved our ability of diagnosing spina bifida but also be a simple, economical and readily available alternative to MRI. Keywords: Spina Bifida, Ultrasonography, Sensitivity